Changes in Organizational Culture of UISU Private Sma Pematangsiantar - Dian Ratna Puri; Nathanael Sitanggang; Joharis Lubis (CV. Inara, 2021)
This study aims to describe the impact of changes in Organizational Culture at SMA UISU Pematangsiantar as a result of changes in the organizational structure set by the principal and explain how to solve problems that occur due to changes in organizational culture. The method used in this research is a qualitative case study. The instruments used are interviews, observation and documentation studies. Interviews were conducted on informants, namely the principal and supported by supporting informants consisting of representatives of the principal in the curriculum field, vice principal for student affairs, and teachers at UISU Pematangsiantar High School. Researchers conduct interviews at different times and places, researchers conduct interviews with unstructured methods so that researchers are more free to ask questions.